Discrimination Against Sexual Minorities in Education and Housing : Evidence from Two Field Experiments in Serbia - World Bank (World Bank, Washington, DC, 2018)
Discrimination against lesbian, gay, bisexual, transgender and intersex (LGBTI) people is widespread and LGBTI exclusion from economic markets, vital services and political spaces is entrenched. This is not just a personal problem, it is a development challenge; not only because discrimination is inherently unjust, but also because "there are substantial costs—social, political, and economic—to not addressing the exclusion of entire groups of people." Understanding the barriers LGBTI people face in accessing markets, services, and spaces is important for designing more inclusive policies and programs.